(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article presents the data of aquatic plants that are used for fodder purposes to increase the productivity of fish. in the example of an aquatic plant duckweed minor, data on the chemical composition of aquatic plants are described.